Dynamic supply chain capabilities : a case of oil and gas industry in Malaysia - Shatina, Saad (2016)
Supply chain (SC) is a dynamic process that entails continuous flow of information, materials and funds across multiple functional areas, within and between chain members to meet customer’s requirements and to maximize profit. However, organizations may encounter problems related to the dynamic process in SC. Oil and gas (O&G) industry is one of the SC entities which require dynamic processes of capabilities due to high degree of uncertainties. Motivated by the complexity and uncertainty of SC, this study intends to understand the concept of dynamic supply chain capabilities in the organizations specifically in Malaysia environment. The study focuses on the firm’s capabilities dimensions as well as the influence of the environmental uncertainties on dynamic supply chain capabilities dimensions of the O&G industry. Previous literatures related to supply chain management, and dynamic capabilities were reviewed to support the study. The researcher analyzed multiple cases from the perspectives of the O&G players in Malaysia via qualitative research methodology. Nine managers of services contractors and one manager of production sharing contractor were selected for interviews to share experiences on the needs for dynamic supply chain capabilities. Results showed that value chain coordination, client, supplier and operations are important in the SC orientation; knowledge accessing and coevolving are vital to the dynamic supply chain capabilities; finally, ethics and professional values, and technology driven are important in the environmental uncertainties. Such findings are necessary for emergent framework of dynamic supply chain capabilities on how O&G industry can benefit. Hence, the main contributions of the research findings are: (i) contribution to the body of knowledge in developing better understanding on the dimensions of dynamic supply chain capabilities towards strategies; and (ii) contribution to the managerial in understanding and capturing emergent dimensions of dynamic supply chain capabilities by providing a basis for future analysis.